Runoff Prediction by Linear Discrete Input-output Model - Kumar, Parvendra; Singh, J K; Singh, S B (Journal of Agricultural Engineering, 2008)
A mathematical model incorporating discrete linear input-output approach for Karkara watershed of Tilaiya dam catchment in Upper Damodar Valley of Jharkhand State of India was developed for estimating direct runoff hydrographs on storm basis. In this model, the rainfall data in blocks of finite duration are represented by the unit-step function. The direct runoff hydrograph ordinates are obtained directly as the inverse Laplace transform of the product of Laplace transform of the input and the transfer function (i.e. Laplace transform of instantaneous unit hydrograph) of the system. The parameters of the model were estimated by the methods of cumulants and moments using rainfall and runoff data of the watershed. The performance of the model was tested by comparing the computed direct runoff hydrographs with the observed runoff hydrographs. The model was calibrated for nine storm events and validated for three storm events. Performance evaluation indices indicated that the lag and route model worked well for the study area.